Comparison of upwind and characteristic schemes for solving multiphase diffusion-convection equation - Pieskä, Jali; Laitinen, Erkki (Computer Assisted Methods in Engineering and Science, 2023)
In this paper the multiphase diffusion-convection problem is solved numerically by using upwind and characteristic schemes. Discretization for the schemes are performed by finite difference method. For solving the algebraic equations on every time level the modified S.O.R. method is used. In the numerical results computing time, number of iterations and accuracy of the schemes are analysed.